2015
DOI: 10.2217/epi.15.92
|View full text |Cite
|
Sign up to set email alerts
|

Merging Data from Genetic and Epigenetic Approaches to Better Understand Autistic Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that is characterized by a wide range of cognitive and behavioral abnormalities. Genetic research has identified large numbers of genes that contribute to ASD phenotypes. There is compelling evidence that environmental factors contribute to ASD through influences that differentially impact the brain through epigenetic mechanisms. Both genetic mutations and epigenetic influences alter gene expression in different cell types of the brain. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 186 publications
1
28
0
Order By: Relevance
“…In addition, Voineagu et al showed that the transcriptome changes they observed in the ASD brains converge with GWAS data, which are enriched for neuronal genes, in particular genes coding for synaptic proteins; immune changes have a less pronounced genetic component, suggesting that the differential expression found in ASD is secondary [58]. This idea is consistent with the key role of microglia in synaptic pruning [5961]. A reasonable hypothesis is that a primary defect in neurons leading to dysfunctional synaptogenesis is triggering microglial activation and synaptic pruning, which is then reflected in the postmortem gene expression findings.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, Voineagu et al showed that the transcriptome changes they observed in the ASD brains converge with GWAS data, which are enriched for neuronal genes, in particular genes coding for synaptic proteins; immune changes have a less pronounced genetic component, suggesting that the differential expression found in ASD is secondary [58]. This idea is consistent with the key role of microglia in synaptic pruning [5961]. A reasonable hypothesis is that a primary defect in neurons leading to dysfunctional synaptogenesis is triggering microglial activation and synaptic pruning, which is then reflected in the postmortem gene expression findings.…”
Section: Discussionmentioning
confidence: 72%
“…In addition the offspring show impaired motor coordination and motor learning ability coupled with a reduction in the cerebellar size and impairment in the cerebellar foliation profile [263,264]. A 3 day exposure to 2.5 mg/kg tretinoin (gestational days [11][12][13] produces a 10% reduction in weight of cerebellum at 4 weeks of age, not accompanied by other malformations [265]. In rats treated with retinoic acid at gestational day E10, the foetuses show structural changes similar to humans with Arnold-Chiari malformation, including downward displacement of the cerebellum to just above the foramen magnum and compression of the developing medulla into a small posterior fossa [266].…”
Section: Cosmetic Ingredients Targeting Autism Genesmentioning
confidence: 99%
“…Epigenetic changes have been observed in autism, and these too may be related to environmental agents [12,13] as reported for Bisphenol A and heavy metals (see Table 1) and for flame retardants and other endocrine disruptors, including soy formula and phytoestrogens such as genistein [14][15][16] and also for other nutritional agents such as Vitamin D and folic acid [17][18][19]. However, epigenetics is not the subject of this study, which is limited to the 206 autism-related polymorphic genes reported from gene association studies.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by impaired social interactions, language deficits, as well as, restrictive or repetitive behaviors. As recently iterated (Grayson and Guidotti, 2016; Zhubi et al, 2014a), to better understand the complexity of ASD etiopathogenesis, it is essential to conceptualize genetic and environmental factors as complementary factors that modify ASD risk through changes in gene expression. Environmental factors and genetic background interact and amplify the contribution of individual components.…”
Section: Introductionmentioning
confidence: 99%